Sixth International congress on industrial and applied mathematics (ICIAM 07) - International congress on industrial and applied mathematics (16-20 Jul 2007: Zurich, Switzerland); Jeltsch, Rolf; Wanner, Gerhard (Switzerland : European Mathematical Society, 2009)
The International Council for Industrial and Applied Mathematics (ICIAM) is the worldwide organisation of societies which are dedicated primarily of significantly to applied and/or industrial mathematics. The ICIAM Congresses, held every 4 years, are run under the auspices of the Council with the aim to advance the applications of mathematics in all parts of the world. The 6th ICIAM Congress was held in Zurich, Switzerland, 16-20 July 2007, and was attended by more than 3000 scientists from 47 countries." "This volume collects the invited lectures of this Congress, the appreciations of the ICIAM Prize winners' achievements and the Euler Lecture celebrating the 300th anniversary of Euler. The authors of these papers are leading researchers of their fields, rigorously selected by a distinguished international program committee. The book presents an overview of contemporary applications of mathematics, new perspectives and open problems.
Invited lectures.
Keywords: Mathematics -- Congresses